PERTANGGUNGJAWABAN PIDANA TERHADAP ANAK NAKAL (JUVENILE DELINQUENCY) DALAM PEMBUATAN KONTEN BERBAHAYA - Rifky Revanza Kaya (2023)
The development of Information and Technology has resulted in internet and social media users now increasingly widespread, including children. This has also led to an increase in Juvenile Delinquency. Many cases involve Juvenile Delinquency to perform dangerous acts in the act of harmful content on social media. This research will discuss the issue of how criminal liability for Juvenile Delinquency in the creation of harmful content and how efforts to optimize law enforcement along with legal protection of Juvenile Delinquency in the creation of harmful content. The research method used in this study is a normative juridical research method with a problem approach method that includes a statutory approach, a case approach, and a conceptual approach. The results of the research found are that in criminal liability for delinquent children in acts of harmful content, it is necessary to know in advance the age of the child so that it can be known which age category of the child is included in order to be able to account for his actions and it is necessary to know the criminal elements that have been violated to be processed in accordance with the Juvenile Criminal Justice System Law. In addition, legal protection must be carried out both preventively and repressively so that the purpose of protecting the rights of children can be guaranteed. The author hopes that various parties can cooperate well in tackling and preventing criminal cases involving delinquent children because basically the child is affected by a bad environment and has a vulnerable mental state situation.